The Palaeontological Heritage of Boulemane Between Illegal Looting and Geoconservation: Issues, Challenges and Solutions - Kawtar Ech-charay; Khadija Boumir; Susannah C. R. Maidment; Ahmed Oussou; Richard J. Butler; Mustapha Ouaskou; Abdessalam El Khanchoufi; Driss Ouarhache (Geoheritage, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Effects of environmental conditions on mate fidelity in a socially monogamous seabird - Sue Lewis; Adam Butler; Sarah Wanless; Mark A. Newell; Michael P. Harris; Sarah J. Burthe; Carrie M. Gunn; Richard J. Howells; Francis Daunt (Animal Behaviour, 2025)

First dinosaur remains from Serbia: Sauropod and theropod material from the uppermost Cretaceous (Maastrichtian) of Osmakovo - Zoran Marković; Miloš Milivojević; Richard J. Butler; Paul M. Barrett; Simon Wills; Andrew A. van de Weerd; Wilma Wessels; Predrag Radović (Cretaceous Research, 2025)

Determining the relative scientific and cultural “value” of the UK's in-situ dinosaur track sites - Kirsty M. Edgar; Richard J. Butler; Jonathan G. Larwood; Joshua J.P. Smith (Proceedings of the Geologists' Association, 2025)

Use of multiple climate change scenarios to predict future distributions of alligator gar (Atractosteus spatula) in the United States - Jory Bartnicki; Richard A. Snow; Andrew T. Taylor; Christopher J. Butler (Environmental Biology of Fishes, 2024)

Thermal exposure risk in different life stages of Chinook salmon in the Nechako River system, British Columbia - Muhammed A. Oyinlola; Mostafa Khorsandi; Noa B. Mayer; Natalie Butler; Jacey C. Van Wert; Erika J. Eliason; Richard Arsenault; Colin J. Brauner; Scott G. Hinch; Andre St-Hilaire (Climatic Change, 2024)

Cyclones and skinny dolphins: adaptation pathways for Pacific communities under rapid global change - Matthew J. Colloff; James R.A. Butler; Nat Burke; John Morley; Lorrae van Kerkhoff; Zelda Hilly; Richard B. Makini-Purcell; Jamal Namo; Remy Barua; Kathryn Michie; Minnie Rafe; Slade Ririmae (Climate and Development, 2024)

Air pollution and the sequelae of COVID-19 patients: A multistate analysis - Michael Jerrett; Claudia L. Nau; Deborah R. Young; Rebecca K. Butler; Christina M. Batteate; Ariadna Padilla; Sara Y. Tartof; Jason Su; Richard T. Burnett; Michael J. Kleeman (Environmental Research, 2023)

Colocalization of expression transcripts with COVID-19 outcomes is rare across cell states, cell types and organs - Julian Daniel Sunday Willett; Tianyuan Lu; Tomoko Nakanishi; Satoshi Yoshiji; Guillaume Butler-Laporte; Sirui Zhou; Yossi Farjoun; J. Brent Richards (Human Genetics, 2023)
Identifying causal genes at GWAS loci can help pinpoint targets for therapeutic interventions. Expression studies can disentangle such loci but signals from expression quantitative trait loci (eQTLs) often fail to colocalize—which means that the genetic control of measured expression is not shared with the genetic control of disease risk. This may be because gene expression is measured in the wrong cell type, physiological state, or organ. We tested whether Mendelian randomization (MR) could identify genes at loci influencing COVID-19 outcomes and whether the colocalization of genetic control of expression and COVID-19 outcomes was influenced by cell type, cell stimulation, and organ. We conducted MR of cis -eQTLs from single cell (scRNA-seq) and bulk RNA sequencing. We then tested variables that could influence colocalization, including cell type, cell stimulation, RNA sequencing modality, organ, symptoms of COVID-19, and SARS-CoV-2 status among individuals with symptoms of COVID-19. The outcomes used to test colocalization were COVID-19 severity and susceptibility as assessed in the Host Genetics Initiative release 7. Most transcripts identified using MR did not colocalize when tested across cell types, cell state and in different organs. Most that did colocalize likely represented false positives due to linkage disequilibrium. In general, colocalization was highly variable and at times inconsistent for the same transcript across cell type, cell stimulation and organ. While we identified factors that influenced colocalization for select transcripts, identifying 33 that mediate COVID-19 outcomes, our study suggests that colocalization of expression with COVID-19 outcomes is partially due to noisy signals even after following quality control and sensitivity testing. These findings illustrate the present difficulty of linking expression transcripts to disease outcomes and the need for skepticism when observing eQTL MR results, even accounting for cell types, stimulation state and different organs.

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

The condition, use and future of the UK's largest accessible dinosaur tracksite at Spyway Quarry, Dorset - Kirsty M. Edgar; Luke E. Meade; Harry T. Jones; Lewis Haller; Sam Scriven; Christopher Reedman; Richard J. Butler (Proceedings of the Geologists' Association, 2023)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Negative Food Effect of Danirixin: Use of PBPK Modelling to Explore the Effect of Formulation and Meal Type on Clinical PK - Richard S. Lloyd; Martin I. Hingle; Jackie C. Bloomer; Stephen J. Charles; James M. Butler; Alan Paul; Xiaofeng Zhu; Bruce Miller; Donald D’Amico; Alison Donald; Ruth Tal-Singer; Claire Ambery (Pharmaceutical Research, 2020)

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Chromium, manganese, nickel, and cobalt mobility and bioavailability from mafic-to-ultramafic mine spoil weathering in western Massachusetts, USA - Justin A. Mistikawy; Trevor J. Mackowiak; Mark J. Butler; Ivan C. Mischenko; Richard S. Cernak; Justin B. Richardson (Environmental Geochemistry and Health, 2020)

Using genetics to inform restoration and predict resilience in declining populations of a keystone marine sponge - Sarah M. Griffiths; Evelyn D. Taylor-Cox; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Biodiversity and Conservation, 2020)
Genetic tools can have a key role in informing conservation management of declining populations. Genetic diversity is an important determinant of population fitness and resilience, and can require careful management to ensure sufficient variation is present. In addition, population genetics data reveal patterns of connectivity and gene flow between locations, enabling mangers to predict recovery and resilience, identify areas of local adaptation, and generate restoration plans. Here, we demonstrate a conservation genetics approach to inform restoration and management of the loggerhead sponge ( Spheciospongia vesparium ) in the Florida Keys, USA. This species is a dominant, habitat-forming component of marine ecosystems in the Caribbean region, but in Florida has suffered numerous mass mortality events. We developed microsatellite markers and used them to genotype sponges from 14 locations in Florida and a site each in The Bahamas, Belize and Barbuda. We found that genetic diversity levels were similar across all sites, but inbreeding and bottleneck signatures were present in Florida. Populations are highly structured at the regional scale, whilst within Florida connectivity is present in a weak isolation by distance pattern, coupled with chaotic genetic patchiness. Evidence of a weak barrier to gene flow was found in Florida among sites situated on opposite sides of the islands in the Middle Keys. Loggerhead sponge populations in Florida are vulnerable in the face of mass mortalities due to low connectivity with other areas in the region, as well as distance-limited and unpredictable local connectivity patterns. However, our discovery of Florida’s high genetic diversity increases hope for resilience to future perturbations. These results provide valuable insight for sponge restoration practice in Florida.

Evaluation of heat stress and cumulative incidence of acute kidney injury in sugarcane workers in Guatemala - Jaime Butler-Dawson; Lyndsay Krisher; Hillary Yoder; Miranda Dally; Cecilia Sorensen; Richard J. Johnson; Claudia Asensio; Alex Cruz; Evan C. Johnson; Elizabeth J. Carlton; Liliana Tenney; Edwin J. Asturias; et al. (International Archives of Occupational and Environmental Health, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Correction to: Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2019)

Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2018)

Biophysical connectivity explains population genetic structure in a highly dispersive marine species - Nathan K. Truelove; Andrew S. Kough; Donald C. Behringer; Claire B. Paris; Stephen J. Box; Richard F. Preziosi; Mark J. Butler (Coral Reefs, 2017)

Resistance to Spongospora subterranea induced in potato by the elicitor β-aminobutyric acid - M. Loreto Hernandez Maldonado; Richard E. Falloon; Ruth C. Butler; Anthony J. Conner; Simon R. Bulman (Australasian Plant Pathology, 2015)

Genetic evidence from the spiny lobster fishery supports international cooperation among Central American marine protected areas - Nathan K. Truelove; Sarah Griffiths; Kim Ley-Cooper; James Azueta; Isaias Majil; Stephen J. Box; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Conservation Genetics, 2015)

Landscape and climate determine patterns of spread for all colour morphs of the alien ladybird Harmonia axyridis - Bethan V. Purse; Richard Comont; Adam Butler; Peter M. J. Brown; Clare Kessel; Helen E. Roy (Journal of Biogeography, 2015)
Aim Understanding why some areas are more vulnerable to invasion by invasive alien species than others represents a key challenge in invasion biology. We investigated the roles of landscape, climate, proximity to initial invasion sites, recording intensity and colour pattern polymorphism in explaining the spread of the invasive ladybird Harmonia axyridis across Great Britain. Location The British mainland and inshore islands (Anglesey, Isle of Wight and the Inner Hebrides). Methods Patterns in time to invasion of H. axyridis were quantified at a hectad level (10 km grid squares) from over 23,000 records. Bayesian spatial survival models were developed relating spread patterns to concurrent patterns in climate, land cover and recording intensity. Separate models were developed for melanic (f. conspicua and f. spectabilis ) and non‐melanic (f. succinea ) colour forms that were hypothesized to differ in their response to climate factors, particularly temperature, and subsequent spread. Results Harmonia axyridis spread more rapidly into hectads containing a high proportion of urban land cover and marginally more slowly into hectads containing high conifer cover. Invasions were recorded more rapidly in hectads with high recording intensity, or that were close to initial invasion sites. Harmonia axyridis colour morphs spread to similar extents, although increased sunshine significantly enhanced the spread of the non‐melanic form (f. succinea ). Correspondence between observed and predicted times of invasion from survival models was substantial (Pearson's r p for all H. axyridis colour forms = 0.834). Main conclusions The ability of H. axyridis to use a wide range of habitats and prey species and overwinter inside buildings may have allowed this species to establish rapidly in urban areas. Native ladybird species in urban areas may suffer combined negative impacts of habitat deterioration and competition from H. axyridis . Spatial survival models help us to identify areas vulnerable to invasion and to understand the impacts of multiple environmental drivers on the spread of invasive alien species, given detailed data on time to invasion.

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

A temperate palaeodiversity peak in Mesozoic dinosaurs and evidence for Late Cretaceous geographical partitioning - Philip D. Mannion; Roger B. J. Benson; Paul Upchurch; Richard J. Butler; Matthew T. Carrano; Paul M. Barrett (Global Ecology and Biogeography, 2012)
Aim Modern biodiversity peaks in the tropics and declines poleward, a pattern that is potentially driven by climate. Although this latitudinal biodiversity gradient (LBG) also characterizes the marine invertebrate fossil record, distributions of ancient terrestrial faunas are poorly understood. This study utilizes data on the dinosaur fossil record to examine spatial patterns in terrestrial biodiversity throughout the Mesozoic. Location We compiled data on fossil occurrences across the globe. Methods We compiled a comprehensive dataset of Mesozoic dinosaur genera (738), including birds. Following the utilization of sampling standardization techniques to mediate for the uneven sampling of the fossil record, we constructed latitudinal patterns of biodiversity from this dataset. Results The dominant group of Mesozoic terrestrial vertebrates did not conform to the modern LBG. Instead, dinosaur diversity was highest at temperate palaeolatitudes throughout the 160 million year span of dinosaurian evolutionary history. Latitudinal diversity correlates strongly with the distribution of land area. Late Cretaceous sauropods and ornithischians exhibit disparate LBGs. Main conclusions The continuity of the palaeotemperate peak in dinosaur diversity indicates a diminished role for climate on the Mesozoic LBG; instead, dinosaur diversity may have been driven by the amount of land area among latitudinal belts. There is no evidence that the tropics acted as a cradle for dinosaur diversity. Geographical partitioning among major clades of herbivorous dinosaurs in the Late Cretaceous may result from the advanced stages of continental fragmentation and/or differing responses to increasing latitudinal climatic zonation. Our results suggest that the modern‐day LBG on land was only established 30 million years ago, following a significant post‐Eocene recalibration, potentially related to increased seasonality.

Palaeoenvironmental controls on the distribution of Cretaceous herbivorous dinosaurs - Richard J. Butler; Paul M. Barrett (The Science of Nature, 2008)

Palaeoenvironmental controls on the distribution of Cretaceous herbivorous dinosaurs - Richard J. Butler; Paul M. Barrett (The Science of Nature, 2008)

Dinosaur remains from the La Quinta Formation (Lower or Middle Jurassic) of the Venezuelan Andes - Paul M. Barrett; Richard J. Butler; Scott C. Moore-Fay; Fernando E. Novas; John M. Moody; James M. Clark; Marcelo R. Sänchez-Villagra (PalZ, 2008)

Larval mortality during export to the sea in the fiddler crab Uca minax - Renae J. Brodie; Richard Styles; Stephen Borgianini; Jenice Godley; Khayree Butler (Marine Biology, 2007)